Case report: Alexander's disease with “head drop” as the main symptom and literature review - Yuan, Yujun; Wu, Qiong; Huo, Liang; Wang, Hua; Liu, Xueyan (Frontiers in Neurology, 2022)
Abstract: Alexander's disease is a rare autosomal dominant hereditary disorder caused by mutations in GFAP gene, which encodes the glial fibrillary acidic protein. The disease has many clinical manifestations, and the onset of the disease spans a wide range of ages, from newborns to children, adults, and even the elderly. The overaccumulation of expression of GFAP has a close causal relationship with the pathogenesis of Alexander's disease. Usually, the disease has severe morbidity and high mortality and can be divided into three distinct subgroups based on the age of clinical presentation: infantile (0–2 years), juvenile (2–13 years), and adult (>13 years). Children often present with epilepsy, macrocephaly, and psychomotor retardation, while adolescents and adults mainly present with muscle weakness, spasticity, and bulbar symptoms. Atonic seizures are a type of epilepsy that often appear in Lennox–Gastaut syndrome and myoclonic-astatic epilepsy in early childhood; however, the prognosis is often poor. Atonic episodes are characterized by a sudden or frequent reduction in muscle tone that can be local (such as head, neck, or limb) or generalized. Here, we report a 4-year-old girl whose main symptoms were intermittent head droop movements, which could break the frontal frame and bleed in severe conditions. A video-encephalography showed that the nodding movements were atonic seizures. A head magnetic resonance imaging revealed abnormal signals in the bilateral paraventricular and bilateral subfrontal cortex. The gene detection analyses indicated that GFAP gene exon 1 c.262 C>T was caused by heterozygous mutation, as both her parents were wild-type. The girl had no other abnormal manifestations except atonic seizures. She could communicate normally and go to kindergarten. After oral administration of sodium valproate, there were no atonic attacks. Although epilepsy is a common symptom of Alexander's disease, atonic seizures have not been reported to date. Therefore, we report a case of Alexander's disease with atonic seizures as the main symptom and provide a review of the literature.